Electronic Properties of Cs‐Based Halide Perovskites: An Ab Initio Study. Issue 17 (6th February 2018) - Moschou, Georgia; Koliogiorgos, Athanasios; Galanakis, Iosif
Abstract : Halide perovskites consist a class of materials under intense investigation due to their potential technological applications like solar cells, optoelectronic devices, and catalysis. Recently, the cubic MABX3 compounds have been studied using electronic band structure calculations from first principles [A. Koliogiorgos et al., Comput. Mater. Sci .2017, 138, 92], where MA stands for the methylammonium cation, B is a divalent cation, and X a halogen. In this paper, the study in the case where Cs stands in place of the MA cation is expanded. The results suggest that the Cs‐based compounds exhibit also a variety of lattice constants and energy band gaps. The calculated equilibrium lattice constants differ substantially from the experimental ones. The calculated energy gaps also show large deviations for these lattice constants. Moreover, the use of more sophisticated functionals leads to conflicting changes in the energy gap values and its effect is materials dependent. The results suggest that contrary to the MA halide perovskites, the Cs halide perovskites consist a more delicate case and there is still a long way for ab initio calculations to accurately describe their structural and electronic properties. Abstract : Perovskites consist a large family of materials with a large variety of interesting technological applications. In the present study, using ab initio electronic band structure methods the halide perovskites containing Cs and having the chemical formula CsBX3 is modeled, where B is a divalent cation and X a halogen. Employing various functionals for the exchange‐correlation energy, the equilibrium lattice constant, the density of states, and the width of the energy band gap are determined.